4. CHARACTERISTICS OF LEUKOCYTE PARAMETERS IN PATIENTS WITH ACUTE PANCREATITIS TREATMENT AT TRA VINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To investigate the characteristics of leukocyte parameters in patients with acute pancreatitis treated at Tra Vinh General Hospital.Methods: Descriptive cross-sectional study using retrospective and prospective data in medical records on 154 patients with acute pancreatitis with indications for blood count test treated at Tra Vinh General Hospital from June 2024 to August 2024.Results: Abnormalities compared to the hematological reference range were recorded in indicators such as high WBC group accounting for 71.43%, high NEU group accounting for 79.87%. Increased amylase concentrations were associated with normal and high WBC index and normal LYM index. The study recorded many correlations between amylase concentration levels and leukocyte parameters in acute pancreatitis patients such as WBC, NEU, LYM.Conclusion: Blood count testing is an indispensable part for patients with acute pancreatitis. It is necessary to pay attention to the WBC, NEU, and LYM indices to evaluate the patient's inflammation level.
Keywords: Blood count; acute pancreatitis.